Analysis of the Implementation of International Standards on Auditing (ISA) in Internal Audit Practice at the Puskopdit Swadaya Utama with the Agency Theory Approach - Mage, Urbanus Berni; Konstantinus Pati Sanga; Fransiscus De Romario (International Publisher (YAPENBI), 2024)
This research aims to analyze the implementation of International Standards on Auditing (ISA) in internal audit practices at Puskopdit Swadaya Utama Maumere using the Agency Theory approach. This approach is used to understand the relationship between cooperative management as agents and cooperative members as principals in ensuring transparency and accountability. This research uses a qualitative method with a case study approach, where data is obtained through interviews, observation and document analysis. The research results show that Puskopdit Swadaya Utama has not fully implemented ISA standards. Some implementation indicators, such as internal control and documentation of audit procedures, have been implemented partially. However, there are obstacles in terms of limited human resources who understand the ISA standards in depth, as well as a lack of adequate technological support. In conclusion, although there are initial steps towards implementing ISA, greater efforts are needed to increase the capacity of internal auditors, strengthen oversight policies, and integrate technology that supports audit practices. It is hoped that the recommendations provided will help Puskopdit achieve more optimal audit standards in order to increase member trust and make cooperative management more transparent.